Idiopathic intracranial hypertension: Pathophysiology, diagnosis and management - Wang, Michael T.M.; Bhatti, M. Tariq; Danesh-Meyer, Helen V. (Journal of clinical neuroscience, 2022)
•The population burden of IIH is projected to rise with increasing rates of obesity.•Recent studies highlight the pathogenic role of metabolic and hormonal factors.•Neuroimaging and lumbar puncture assessment are required for the diagnosis of IIH.•A majority of IIH patients respond to weight loss and/or acetazolamide therapy.•Surgical interventions are available for those refractory to medical treatment. Idiopathic intracranial hypertension (IIH) is characterized by increased intracranial pressure, manifested by papilledema and radiological findings, in the absence of an identifiable casual factor. The primary symptoms include headache, vision loss, and pulsatile tinnitus, and are recognized to have profound impacts on quality of life and visual function. IIH demonstrates a strong predilection towards obese women of reproductive age, and the population incidence is rising with the growing prevalence of obesity worldwide. The pathophysiology involves dysregulation of cerebrospinal fluid (CSF) dynamics and venous sinus pressure, and recent studies highlighting the pathogenic role of metabolic and hormonal factors have led to the identification of several pharmacological targets and development of novel therapeutic agents. The overarching treatment goals include symptomatic alleviation and prevention of permanent vision loss. The Idiopathic Intracranial Hypertension Treatment Trial, the first of its kind randomized controlled trial on IIH, provides class I evidence for treatment with weight loss and acetazolamide. In medically refractive or fulminant cases, optic nerve sheath fenestration, CSF diversion, and venous sinus stenting, have been successfully implemented. However, there are few high-quality prospective studies investigating the treatment and natural history of IIH, highlighting the compelling need for further research to determine the optimal treatment regimen.